Interest Rate Spreads in English-Speaking African Countries - Crowley, Joe (IMF Working Papers; Working Paper ;, 2007)
This paper examines interest rate spreads in English-speaking African countries. Higher spreads were found to be associated with lower inflation, a greater number of banks, and greater public ownership of banks. Higher deposit interest rates were found to be associated with lower interest rate spreads, but higher net interest margins. A large increase in spreads in the late 1980s and 1990s may be explained by a strengthening of financial sector supervision. Limited data suggested that poor governance, weak regulatory frameworks and property rights, and higher required reserve ratios are associated with higher spreads.